Emotional intelligence of dental students and its correlation with leadership behaviour - SR, Sara; Y, Farinawati; SI, Fahd; A, Mahadir; AF, Azizah (Penerbit Universiti Kebangsaan Malaysia, 2023)
Leadership, the art of motivating oneself and others towards achieving a common goal, is crucial for dental students to prepare themselves as future leaders that able to promote dental healthcare. Emotional intelligence (EI) is the ability to understand, utilise and manage emotions in positive ways may highly influence the self-leadership (SL) level among dental undergraduates and potentially become a meaningful predictor for SL development. The objectives of this study was to find out the influence of EI on dental undergraduates’ SL and to assess the significance of the demographic factors (e.g. university of study, level of academic study and gender) on the students’ SL. A cross-sectional study performed in 2020-2021 involving dental undergraduates at two universities in Kurdistan (Hawler Medical University [HMU] and University of Duhok [UOD]) and one of university in Malaysia (Universiti Kebangsaan Malaysia [UKM]). Dental students (N=236) participated in the study answering two questionnaires; The Schutte-Self Report EI Test (SSREIT) and the Revised-Self Leadership Questionnaire (RSLQ). Results showed a significant correlation between EI and SL (p<0.01) with 37% of the variation in SL determined by EI. SL among dental undergraduates in Malaysia were higher than in Kurdistan. Females had better SL compared to males. Response rate was 70%, 43% and 59% in HMU, UOD and UKM respectively. As a conclusion EI has huge influence on SL of dental undergraduates and therefore, EI is a fundamental element that needs to be considered for the leadership development among dental students. Apart from EI, gender and university of study also demonstrated significant influence on SL of dental undergraduates.